Yapı Üretiminde Toplam Kalite Yönetimi Ve Kerpiç Yapı Üretiminde Uygulanması - Tülbentçi, Tuğşad (Fen Bilimleri Enstitüsü, 1998)
Bu çalışmada, son yıllarda kullanıcılara sunulan ürün veya hizmetlerde aranan en önemli özellik olan "kalite" ve kalite ile ilgili kavramlar geniş olarak incelenmiştir. Dünya nüfusunun hızla artması, beraberinde konut ihtiyacım da getirmektedir. Birçok üretim sektörüne lokomotiflik yapan yapı üretim sektöründe kaliteyi sağlamak, "ileri yönetim teknikleri" olarak adlandırılan yönetim sistemleri ile mümkün olabilmektedir. Diğer üretim sektörlerinden sağlanan girdilerin belirli bir kalite düzeyinde tutulabilmesi, Kalite Kontrol ve Yönetim sistemleri ile sağlanabilmektedir. Altı ana bölümden meydana gelen tezin ilk bölümünde kalite ve ilgili kavramları kısaca tanımlanarak diğer bölümlere ait ön bilgilerin verilmesi ve konulara giriş amaçlanmıştır. İkinci bölümde, kalite ve kalite ile ilgili kavramların tanımlan ve temel prensiplerine yer verilmiş, kalitenin sağlanması için gerekli olan spesifikasyonları belirleyen Kalite Güvencesi ve ISO 9000 açıklanmış ve kaliteyi sağlamak açısından son derece büyük önem taşıyan Toplam Kalite Kontrolü ve temel prensipleri tanımlanmıştır. Tezin üçüncü bölümünde Toplam Kalite Yönetimi tanımlanmış, sırasıyla Toplam Kalite Yönetiminin temel ve prensipleri, amaçları ve yararlan, aşamaları, organizasyonu ve maliyetleri açıklanmış, en sonunda da "sürekli gelişim" anlamım taşıyan Japon kalite kavramı "Kaizen" tanımlanmıştır. Dördüncü bölümde, yapı üretiminde Toplam Kalite Yönetiminin uygulanmasının sağlayacağı avantajlar açıklanmıştır, öncelikle yapı ve yapı üretimine, sonra da yapı üretim süreci olarak tanımlanan şantiyenin; yerleşimi, planlaması ve yönetimine deyinilmiştir. Yapı üretiminde Kalite Kontrolünün önemi anlatılarak bu sistemin yapı üretimini nasıl etkilediği ve uygulanma yaklaşımları açıklanmıştır. Beşinci bölümde, kerpiç yapı malzemesi hakkında bilgi verilmiş, geleneksel ve geliştirilmiş (alçı katkılı) kerpiç yapı üretim yöntemleri açıklanarak bu iki sistemin karşılaştırılması yapılmış ve Toplam Kalite Yönetiminin kerpiç yapı üretimine uygulanması sonucunda bu sektörde beklenen değişimler incelenmiştir. Tezin son bölümünde ise Toplam Kalite Yönetiminin uygulanması ile kerpiç yapı üretim organizasyonlarında ortaya çıkan maliyet düşüşleri, ürün, hizmet ve işçilik kalitesindeki artışlar ile işçilik maliyetlerindeki düşüşler, verimlilik, etkinlik ve kârlılıktaki artışlar, kullanıcıların tam tatmini, üretimde kullanılan hammaddelerin yüksek kalitede olması, çevresel kalite anlayışındaki iyileşmeler, rekabet gücü ve pazar payındaki artışlar, çalışanların güvenlik, moral ve motivasyonunun arttırılması ve iyileştirilmesi gibi avantajlar vurgulanmış ve kalite eğitiminin, kişilerin okul eğitimi ile birlikte başlaması ve üniversitelerdeki yüksek eğitim programlarına yerleştirilmesi önerisi ile sonuçlandırılmıştır.

The subject of this thesis depends on "quality" basically and named as "Total Quality Management in Building Production and Investigation of this Title on Adobe Building Production". The aim of this thesis is to determine and emphasise the importance and benefits of utilising quality and quality terms approaches to examine the methods to be utilised in order to achieve quality in building production by the terms of Total Quality Management and develop some proposals related to the "adobe building production" which can conserve innegligible amount of energy during the production phase and even in usage phase and one of the most important cultural buildings of our country. According to ISO 9000 (The International Organisation for Standardisation), the quality is defined as "the totality of features and characteristics of a product or service that bears on its ability to satisfy stated or implied needs". Quality can also be defined as the conformity to reasonable standards and specifications; conformity to usage; satisfying users' needs, wishes and expectations with a competitive price; meeting users needs. In another words, it can be defined in general terms as a suitability degree of the provided product or service to the expected usage goals. If the product is produced appropriately to users' aim, it can be defined as high quality. Quality is not meaning the best, absolutely. A product or service quality depends on its function, using aim and price. Quality also depends on the quality of raw and auxiliary material, sources and technology. Unqualified productions not onh/ decrease the exportable product or service quality but it prevents the expanding of facilities, the increase of living standards, and the welfare of the public and the development as well. Lack of quality also causes to the waste of work-power (man power) and energy. xiu Nowadays, social life of society is affected by two fundamentals. As a result of introduction of electronics to the production technology, the data flow became easier and higher in level. This is the first fundamentaL Expanding of the national markets to regional markets than to global markets caused a great competition among organisations and management. This is the reason that many international organisations and management produce same products indeed. This can supposed to be the second reason. Consequently the meeting of the concepts and conditions of quality became more important as a reason of the improvement of technology and high-level competition. These two fundamentals are the reason of globalisation and these factors activated the improvement and development of quality. So it is more difficuh to provide quality under these conditions. The thesis consists of six chapters. in the first chapter of thesis, introduction to quality and the aim of the studying this thesis were explained. in the second chapter of the thesis, the concepts, the aim, the importance, the basics and the principles of quality were descrîbed. Then the quality, the Quaüty Systems, improvements of Quality Systems and the relation between production and Quaüty Systems were defined. According to the İSO (The international Organisation for Standardisation), Quality Systems can be defined as "the organisational structure, responsibilities, procedures, processes and resources for implementing Quality Control". After the explanation of Quality Systems, the Quality improvement, Ouality Organisation and cost of quality were defined respectively. in the second part of chapter 2, Total Quality, the basics and the principles, the Organisation and the importance of Total Quaüty were explained. Total Quality consists of simultaneously satisfying ali of an organisations' shareholders (if exist), users' (customers) and management employees. Shareholders return on investment, users expect high-quality level products and services, and employees strive for quality of life. Both quality and productivity are necessary for success of the organisations and management. Productivity can not be obtained without quality. Total Quality concepts, helps to obtain productivity while improving and developing quality. in the third part of chapter 2, another quafity term called "Quality Control" was defined and then the facilities and the aims, the basics and the principles, the phases, the Organisation and the cost of Quality Control were explained in order. According to İSO 9000, Quality Control is defined as "the operational techniques and activities those are used to fulfil requirements for quality". Although, Quality Control consists of carrying out lots of functions which are continuously present quality provided for the users' satisfaction, developing, designing, servicing to the users, there is an important subject that is have to clarify which causes confusion of Qualfty Control functions and inspections each other. That has to be clear that inspection is an important part of Quality Control functions but onty includes a specific part. As a result, Quality Control activities can be classified as new design, incoming material controL, product control and special process studies. xiv in tbe fourth part of chapter 2, Quality Assuranee and İSO 900U (Tne Interaatıonal Organisation for Standardisation) were defîned. After the explanation of systematic structure, the basics and the principles and the foıındation phases of Quality Assurance, the aims and the benefits, the basics and the principles and the concepts of İSO 9000 and Quality Assurance were defined respectively. According to İSO, the definition of Quality Assurance is given as "the ali those planned and systematic actions necessary to provide adequate confidence that a product ör service will satisfy given requirements for quality". Quality Assurance system provides to give guarantee to users not to buying any non- conforming product. This action can be done by means of controlling process, instead of inspecting the product So, the defect is determined during the productkm process and corrective action can be started immediately. After the correction of the defect, the product process can be continued by means of giving permission. in order to apply the Quality Assurance in organisations and management, fîrst of ali, the levels should be documented and a quality manual should be formed. Documentation may include quality manuals, description of quality-related procedures, Quality System control reports and other quality records. Ali documentation should be legible, dated (including revision dates), clean, readily identifîable and maintained in an orderly manner. Quality mannals aim to develop the subject, to affect and control the activities in the future. The primary purpose of the quality manual is to provide an adequate description of the Quality Management System while serving as a permanent reference in implementation and maintenance of that system. The organisations and management must also form and apply a Quality Poh'cy of their own organisation. Quality Policy is defined in İSO Standards concerns with quaüty as "the overall quality intentions and direction of an organisation as regards quality, as formally expressed by the top management". The policy should exactly define the "aim related quality". A Quality Management department should be established to determine and apply the Quality Poh'cy. The members of this department should have carrier, experience and knowledge concerning the subject This department determines and implements the Quality Policy. The attainment of. the desired quality requires the commitment and participation of ali members of the organisation. in order to apply the Quatity Management, an efficient Quality System should be established, the procedure, the methods, the resources and the responsibflities should be clear. Ali items should be written in a dynamic structure against the changes that might occur during the time. The purposes of İSO 9000 are clarifying the distinctions and interrelationships among the principal quality concepts and providing the guidelines for the selection and the use of a series of International Standards on Quality Systems. it is not the purpose of the International Standards to standardise Quality Systems implemented by organisations. Building production organisations use these Standards by according to their own needs and conditions. These Standards are the guides those show the way of implication Quality Assurance Systems. in the fifth part of chapter 2, öne of the most important quality tenns called 'Total Quality Control" was defined. Then the aims and the benefits, the basics and the principles, the phases, the organisation and the cost of Total Quality Control were explained respectively. Quality Control department and organisation of Ouality Control were described under the organisation of Total Quality ControL Total Ouality Control is identified as an effective system which integrates the qualfty development, quality maintenance and quafity improvement eflbrt of varîous groups in an organisation so as to enable marketing, engineering, production and services at most economical levels which allow for fiili users' satisfaction. The establishment and successful application of this system in an organisation ör management require great amount of effort Total Quality Control will be öne of the greatest chances of success of the organisations and the management in the sixth part of chapter 2, the conchısions of the chapter explained briefly. in the third chapter of the thesis, the definftions of the management and Ouality Management were given and then the öne of the most important quality term called 'Total Quality Management'' was explained. After the explanation of this term, the basics and the principles, the aims and the benefits, the phases, the organisation and the cost of Total Quality Management explained respectively. Another quality term of Japans' called "Kaizen" defined at last. Ouality Management is "the aspect of the overall management functions that determines and implements the Quality Policy" according to İSO. Total Quality Management is a philosophy and quality process designed to prepare a manufacturer for vvorld class competitiveness. Total Quality Management is a management approach to long-term success through users' satisfaction. Total Ouality Management is a matter of survival organisations and management. That's why, Total Quality Management is a strategic management style in fact Total Ouality Management is a system of management that has users' satisfaction as its primary objective. in Total Ouality Management, the user is anyone within the supply chain that receives materials from a previous step in the supply process. Users can be both internal and external for the organisations and management and include those receiving raw materials, work in process ör finished products. Total Ouality Management systems begin vdth the top management commitment and leadership. Management determines the Total Quality vision and plans for the organisation, and must review and encourage its progress towards the achievement of Total Quality. it is well-known fact that the economic dimension of quality is öne of the most important sides of Total Ouality Management for upper management. Ali these activities are for the purpose of a better profîtable firm in long range. in spite of ali the studies about quality costs, the other side of quality and management's economy of the fîrm relationship has ahvays been neglected. it is very astonishing to realise this fact because there seem to be a close connection between quality and income. As the quality of product increase, the income of management increases too. The behaviours of the users' are the other main factor occurring out of the organisation and affect the sales. xvi Two of the Total Quality Management leaders Deming and Crosby, have some principles about this management system. These principles are also explained in this part of the thesis. Quality Circles are another important part of Total Quality Management. Quality Circles are the activities that must be considered carefully, because they contribute activity (liveliness) to Total Quality Management attempts and promote the team spirit. Quality Improving process is a systematic method of developing products and services and providing users service after the sale based on a through understanding of users' needs and reasonable expectation. In this step, Japans' term "Kaizen" that means gradual unending improvement by doing little things better and setting and achieving increasingly higher standards, is the best description for improvement. Continuous improvement is the basic subject of Kaizen. In continuous improvement, quality of all products, services, processes and employees must be improved and new objectives and goals must be set continuously. Zero defect concept and education are needed for continuous improvement. At the end of chapter 3, a brief explanation was given about the subjects of the chapter, under the heading of conclusion of the chapter. In the fourth chapter of the thesis, the definition of "building" was given and then the relation between the quality of building and designing was described. After the description about building production, the phase of production of building called "site" was defined and the settlement, the planning and the management of the site explained respectively. The responsibilities of the site management were explained under the heading of site management. After the description of the importance of quality and Quality Control in building production, the explanations about quality term in building and building production, application of Total Quality and Quality Control in building production and approaches of quality and Quality Control in building production organisation were defined respectively. It is sure that, the most effective step in forming the quality is "design". If the constructor is determined during design level, this co-operation brings some advantages in practice. The outcome of this co-operation in the design level, is "agreed quality level". If agreed quality level can be determined according to the specifications and standards, the level of the expected quality will be risen. As it is known, one of the most important materials vised for construction of the dwellings of human beings has been adobe for many ancient times. Today, some of the people living in villages and towns also resides in adobe made dwellings. The reason of this arises is from the fact that the soil as a construction material can easily be abundantly obtained and supplied everywhere. xvu It is estimated that one-fourth of the world's population doesn't have adequate housing. An average of 50 % of urban populations lives in slums. In some developing countries, urban slums constitute up to 80% of urban settlements. The housing situation in developing countries will further deteriorate unless substantial resources are allocated to this sector by governments and international aid. The International Labour Office (ILO) will contribute, in the future, to the achievement of the above objectives, especially since the implementation of appropriate housing policies will also generate a great number of much needed employment opportunities. Almost in every place, developing and developed countries, the researches related to soil are made for different purposes. In developing countries, the aim of these researches is to settle the migratory people in houses which one the main component of the settled life. However on the other hand, in developed countries, the aim of these researches is to try to solve the pollution of the environment and energy problems. The developed countries have advanced technology and abandoned constructing the adobe building in a great extent. Using adobe in building production have some advantages such as; it doesn't need much labour; because the amount needed for clay in a soil is not in high percent, clay soil can be found easily; the economic efficiency over other materials because of the heat conservation and low cost of its production; insulation of noise; it prevents environmental pollution and conservation of energy. Because of all these reasons, increasing the market share of adobe will affect the environment positively and will save great amount of national sources. In order to get these benefits, Total Quality Management's principles applied and investigated for adobe building production in the fifth chapter of the thesis. In the fifth chapter of the thesis, application of principles of Total Quality Management on adobe building production was investigated. First of all the properties of the "traditional adobe" such as physical properties, strength of adobe against climatic conditions and mechanical properties were explained. The plasticity and shrinkage properties of adobe were explained under physical properties. Traditional adobe building and production of traditional adobe were described briefly. After the description about traditional adobe, the properties of another kind of adobe which is called "adobe with plaster", were explained. After these explanations, the physical and mechanical properties, and workability and production technology of adobe with plaster were determined. The 622 numbered project of the Scientific Technical Research Council of Turkey called 'T>etermining the Mechanised Construction Technology and Standards for the Gypsum Stabilised Earthen Construction Material" was investigated as an example. Production site and labour of adobe with plaster were determined briefly under production technology. After the comparison of traditional adobe with plaster was made, the principles of Total Quality Management on adobe with plaster were investigated. In order to make mis more clear, the aims, the basics and the principles, the phases, the organisation and the cost of Total Quality Management explained for adobe building production respectively. XVlll In the last chapter of the thesis, the conclusions and proposals were explained. The organisations and management, which apply all the principles of Total Quality Management entirely, get quality in high-level. When these principles are applied in building production organisations, decreases in costs, rises in quality level, rises in labour quality level, decreases İn labour costs, increases in productivity, efficiency and profits, users' full satisfaction, rises in environmental quality, improvements in competition and market sharing, increases in used material quality, motivation of employees can obviously be seen. Because of the reason that adobe building production is a part of building production, these matters written above are current for adobe building production organisations too. That is to say, when the principles of Total Quality Management are applied on the adobe building production, decreases in costs of adobe buildings, rises in quality level of adobe and labour, decreases in labour costs, increases in productivity, efficiency and profits, users' full satisfaction, rises in environmental quality, improvements in competition and market sharing, increases in used material quality, motivation of employees can obviously be obtained. These reasons will affect the preferences of users' for adobe building in a positive way. As the quality is very important for humans-life's standards and health, people have to be educated about quality. In order to be able to success this subject, the education of quality has to be started in primary school and has to go on till university continuously. If the universities' educational programs can be supported by the education of quality, people who graduate from universities can easily apply and manage their knowledge in every phase of their working-life. To sum it up, '^he quality starts with education and ends with education" will be come true. So if this proposal is taken into consideration, the quality of the society's life will be in high- level because of the higher education level of people.
Total Quality Management İn Building Production And Investigation Of This Subject On Adobe Building Production
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1998
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 1998
Keywords: Kerpiç; Toplam kalite yönetimi; Yapı üretimi; Adobe; Total quality management; Structure production